Dampak Konversi Tata Guna Lahan di Daerah Resapan Terhadap Penurunan Cadangan Airtanah di Kabupaten Sleman, Daerah Istimewa Yogyakarta (Effect of Landuse Conversion at Catchment Area to Decrease Groundwater Reserves, In Sleman Regency, Yogyakarta) - ., Sutanto; ., Purwanto; Haty, Intan Paramita (PROMINE, 2015)
Utilization of land use in the Daerah Istimewa Yogyakarta Province resulted in an increase in subsidence and reduced groundwater recharge area of rainwater in catchment areas. The aim of this study was to determine the area of agricultural land were converted to housing, other infrastructure, and the mining area during the last 5 years, as well as to analyze changes in the hydrological system due to land conversion, especially the water supply to the area of the aquifer.     This study is a summary based on secondary data collection, observation and description in the field, measurements of rock permeability and infiltration, as well as laboratory and studio work. Employment in the field is also observed for conversion of land use that occurred and compare the physical properties of rocks before and after conversion. Evaluation is emphasized on the water balance equilibrium calculation has been calculated on the amount of percentage changes in land use and analysis of the impact of the conversion of land use in the catchment area to change the content of groundwater.     Based on the results of the calculation of the projected reserves of groundwater due to land conversion, water reserves and infiltrasiakan volume continued to decline from year to year. This study is expected by the general public is expected to use the existing land well and wisely with regard to groundwater reserves so that it can minimize the reduction in water reserves and infiltration from year to year.Keywords: landuse, groundwater level, catchment area, infiltration, aquifer